EFEKTIVITAS MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI KALIMAT PERSUASIF KELAS 4 - Diana Safitri; Fenny Roshayanti; Farida Nursyahidah (LPPM Universitas Cipta Mandiri, 2024)
The lack of use of innovative learning models and the lack of focus on learners have impacted unsatisfactory student learning outcomes. This study aims to analyze the effectiveness of project-based learning models on the cognitive learning outcomes of fourth-grade students at SDN Plamongansari 02. This research is a quantitative study with a Pre-experimental Design type with One Group Pretest Posttest Design. The sample taken consisted of 24 fourth-grade students from SDN Plamongansari 02, using Purposive Sampling technique, which is a sampling technique determined and selected by the researcher based on certain considerations. The analysis technique used includes normality test, then hypothesis testing using Paired t-test, which shows that the sig. 0.000 is less than 0.05, hence Ho is rejected and Ha is accepted. This means that the average cognitive learning outcomes of learners in the posttest score have reached mastery learning. Then the N_Gain Test obtained a mean N_Gain percentage of 59.1369, thus it can be concluded that the project-based learning model is quite effective to be implemented in fourth-grade classrooms.